2021
DOI: 10.1159/000518890
|View full text |Cite
|
Sign up to set email alerts
|

Early-Life Patterns of Sugar Consumption and Dental Caries in the Permanent Teeth: A Birth Cohort Study

Abstract: Early-life family conditions may presage caries development in childhood. The aim of this study was to evaluate associations between patterns of sugar consumption in early childhood and permanent dentition caries at age 6 years. A cohort enrolled women accessing prenatal care at public health clinics in Porto Alegre, Brazil. Sociodemographic, anthropometric, and dietary data were collected during pregnancy and 6-month, 12-month, and 3-year follow-ups. Calibrated dental examinations occurred at ages 3 and 6 yea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 41 publications
2
5
0
Order By: Relevance
“…The study findings are consistent with the current evidence of an effect of FSI on dental caries, highlighted in recent major reviews [4][5][6][21][22][23]. An increasing number of individual studies, including our own, have further contributed to the evidence of the negative effect of FSI on dental caries [8,[24][25][26]. This body of knowledge has confirmed with high certainty that FSI is a primary determinant of child oral ill-health.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…The study findings are consistent with the current evidence of an effect of FSI on dental caries, highlighted in recent major reviews [4][5][6][21][22][23]. An increasing number of individual studies, including our own, have further contributed to the evidence of the negative effect of FSI on dental caries [8,[24][25][26]. This body of knowledge has confirmed with high certainty that FSI is a primary determinant of child oral ill-health.…”
Section: Discussionsupporting
confidence: 89%
“…Understanding the patterns and magnitude of sugars intake in childhood IRSAD: Index of Relative Socioeconomic Advantage/Disadvantage (1 is the most disadvantaged). 95%CI: 95% confidence intervals A number of cohort studies to date have evaluated the effect of FSI on child dental caries [26][27][28]. Our analysis of maternal sugars consumption since birth of the child identified an effect of maternal sugars consumption on child dental caries experience [29].…”
Section: Discussionmentioning
confidence: 91%
“…ML models identified additional predictors for dental caries development in primary teeth, such as frequent intake of sweet foods and poor parents’ perception of their child’s oral health. These variables are corroborated by previous studies concerning harmful eating practices in childhood (Feldens et al 2021). Moreover, previous studies revealed that poor parents’ perception of their child’s oral health is associated with low demand for preventive dental care and an increase in caries levels (Emmanuelli et al 2021).…”
Section: Discussionsupporting
confidence: 89%
“…A study on Chinese children aged two to five years revealed associations between ECC and SECC with dietary imbalances, high grain consumption, and limited food variety [ 24 ]. Furthermore, household sugar purchases at three years correlate with family sugar consumption, subsequently impacting the incidence of permanent dentition caries [ 25 ]. Thus, advocating for reduced free sugar intake and a balanced, diverse diet emerge as fundamental strategies for ECC prevention [ 23 ].…”
Section: Reviewmentioning
confidence: 99%